INCIDENCE OF STUNTING AND ITS RELATIONSHIP WITH FOOD INTAKE, INFECTIOUS DISEASES, AND ECONOMIC STATUS IN KENDARI, SOUTHEAST SULAWESI, INDONESIA - Akhmad Akhmad; Sahmad Yadi; Ikhwana Farma (Public Health of Indonesia)
Background: Stunting is characterized by inhibition of growth in children that lead to failure in getting normal heights and healthy child's age. It is a public health problem in the working area of Public Health Center of Mata, Kelurahan Mangga Dua in Kendari in 2016.